Development Of Integrated Transportation System To Enhance Inter-District Connectivity In Jayawijaya Regency - Muhamad Fagi Difinubun; Ayu Anggraini Tambunan; Linus Tabuni (LP2M IAIN Palopo, 2025)
Transportation plays a central role in supporting regional development, particularly in areas with challenging geographical conditions such as Jayawijaya Regency in the Papua Mountains Province. To date, approximately 45% of the 27 districts in Jayawijaya still face isolation due to poor road infrastructure. This condition directly impacts community access to markets, public services, and the distribution of goods and services. This study aims to design an integrated transportation system that can improve connectivity between districts by considering local geographical conditions. The method used combines Geographic Information System (GIS) for road network mapping, Integrated Rural Accessibility Planning (IRAP) for priority route planning, and Structural Equation Modeling–Partial Least Squares (SEM-PLS) to analyze the causal relationship between infrastructure quality, connectivity, economic accessibility, and local economic growth. The results of the GIS analysis show significant disparities between districts, with most road networks in poor to very poor condition. The SEM-PLS tabulation data proves that infrastructure quality (X1) has a significant effect on economic accessibility (X3) and economic growth (Y), while connectivity (X2) has no direct effect on growth. The mediation pathway X1→X3→Y proved significant, emphasizing the crucial role of infrastructure as a key factor in development. This study confirms that improving the quality of transportation infrastructure, followed by a strategy for integrating transportation services, is a strategic step to encourage sustainable economic growth in Jayawijaya, particularly in the agriculture, trade, and tourism sectors.